The genera and species of the Brueelia-complex (Phthiraptera: Philopteridae) described by Mey (2017) - Gustafsson, Daniel R.; Bush, Sarah E.; Palma, Ricardo L. (Zootaxa, 2019)
Two large taxonomic revisions of chewing lice belonging to the Brueelia-complex were published independently in 2017: Gustafsson & Bush (August 2017) and Mey (September 2017). However, Mey (2017) was incorrectly dated “Dezember 2016” on the title page. These two publications described many of the same taxonomic units under different names and therefore, the names in Gustafsson and Bush (2017) have priority over the synonyms in Mey (2017). Here we clarify some of the resulting taxonomic confusion. Firstly, we confirm the availability of the genera Guimaraesiella Eichler, 1949 and Acronirmus Eichler, 1953, as well as the status of Nitzschinirmus Mey & Barker, 2014 as a junior synonym of Guimaraesiella. Nine genera were described and simultaneously placed as juniors synonyms by Mey (2017: 182). We agree with his synonymy in seven of them: Australnirmus Mey, 2017 under Saepocephalum Gustafsson & Bush, 2017; Couanirmus Mey, 2017 under Couala Gustafsson & Bush, 2017; Estrildinirmus Mey, 2017 under Mirandofures Gustafsson & Bush, 2017; Harpactiacus Mey, 2017 under Harpactrox Gustafsson & Bush, 2017; Leiothrichinirmus Mey, 2017 under Resartor Gustafsson & Bush, 2017; Manucodiacus Mey, 2017 under Manucodicola Gustafsson & Bush, 2017, and Protonirmus Mey, 2017 under Ceratocista Gustafsson & Bush, 2017. Furthermore, Mey (2017) described and placed Pomatostomiacus as an absolute junior synonym of Sychraella Gustafsson & Bush, 2017; here, we argue that Pomatostomiacus is actually a junior synonym of Anarchonirmus Gustafsson & Bush, 2017. Also, Mey (2017) described and placed Timalinirmus as a probable junior synonym of Turdinirmoides Gustafsson & Bush, 2017; here we argue that Timalinirmus is a valid genus. We place ten more genera from Mey (2017) as junior synonyms, as follows: Callaenirmus Mey, 2017 and Philemoniellus Mey, 2017 under Guimaraesiella Eichler, 1949; Carpodaciella Mey, 2017 under Turdinirmoides Gustafsson & Bush, 2017; Cinclosomatiellum Mey, 2017 under Maculinirmus Złotorzycka, 1964; Koanirmus Mey, 2017 and Tesonirmus Mey, 2017 under Couala Gustafsson & Bush, 2017; Garrulaxeus Mey, 2017 under Priceiella (Camurnirmus) Gustafsson & Bush, 2017; Lycocoranirmus Mey, 2017 under Corvonirmus Eichler, 1944; Neosittiella Mey, 2017 and Plesionirmus Mey, 2017 under Brueelia Kéler, 1936. We accept Melinirmus Mey, 2017 as valid, and Mohoaticus Mey, 2017 as a valid subgenus of Guimaraesiella Eichler, 1949. Also, we provisionally accept Ptilononirmus Mey, 2017 as valid but, until a proper redescription determines its true status, we categorize Ptilononirmus as genus inquirenda. We accept most species described by Mey (2017) as valid, except for two which we place as junior synonyms: Callaenirmus kokakophilus Mey, 2017 under Brueelia callaeincola Valim & Palma, 2015, and Mohoaticus pteroacariphagus Mey, 2017 under Guimaraesiella (Mohoaticus) diaprepes (Kellogg & Chapman, 1902). We agree with Mey’s assessment that four of his new species are junior synonyms of previously described taxa. Furthermore, among the species (subspecies) described by Mey (2017) as new, we establish 31 new generic (subgeneric) combinations, and we regard 16 species as species inquirenda, and three as incertae sedis.